2005
DOI: 10.1093/eurheartj/ehi223
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a ‘master switch gene’ HIF-1α in a porcine model of chronic myocardial ischaemia

Abstract: Ad2/HIF-1alpha increased myocardial perfusion and improved LV function. Plasmid HIF-1alpha was not associated with improvements in any bioactivity endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…Shyu et al (2002) found that HIF-1␣/VP16 reduces infarct size and increases collateral vessel formation in myocardial tissue from rats after acute myocardial infarction (Shyu et al, 2002). A more recent study using an in vivo porcine model of chronic myocardial ischemia demonstrated significant improvement in myocardial perfusion and postischemic left ventricular dysfunction (Heinl-Green et al, 2005). The current study by Luo et al (2006) supports the idea that HIF-1␣/VP16 is capable of up-regulating BNP in cardiomyocytes (Luo et al, 2006).…”
Section: Hif Transcription Factorssupporting
confidence: 70%
“…Shyu et al (2002) found that HIF-1␣/VP16 reduces infarct size and increases collateral vessel formation in myocardial tissue from rats after acute myocardial infarction (Shyu et al, 2002). A more recent study using an in vivo porcine model of chronic myocardial ischemia demonstrated significant improvement in myocardial perfusion and postischemic left ventricular dysfunction (Heinl-Green et al, 2005). The current study by Luo et al (2006) supports the idea that HIF-1␣/VP16 is capable of up-regulating BNP in cardiomyocytes (Luo et al, 2006).…”
Section: Hif Transcription Factorssupporting
confidence: 70%
“…This HIF-1␣͞VP16 construct has been shown to induce improved perfusion in ischemia models in the rabbit hindlimb (17). In porcine models of myocardial ischemia, HIV-1␣͞VP16 induced improved perfusion and left ventricular function when delivered with an adenoviral vector but not by naked plasmid DNA (18). In skeletal muscle, HIF-1␣͞VP16 was shown to induce a more mature angiogeneic response compared with VEGF when DNA encoding either one was administered with an adeno-associated virus vector (19).…”
mentioning
confidence: 97%
“…Similarly, in a porcine model of chronic myocardial ischemia, 21 Ad2HIF over a concentration range from 10 8 to 10 10 viral particles (VP), showed significantly improved perfusion and improved ventricular function after 4 weeks.…”
Section: Modified Hypoxia-inducible Factor (Hif)-1α Transcriptionmentioning
confidence: 98%